RECOLLECTIONS FROM THE EARLY DAYS OF THE PAEC - Qureshi, I. H. (The Nucleus, 2020)
A committee constituted in January 1955 to prepare R&D program for the utilization of nuclear energy, recommended the establishment of the Atomic Energy Commission, which was created on February 24th 1956. Dr. Nazir Ahmad, the first chairman, assumed the office on April 11th, 1956. The commission chalked out the plan of actions and recruited a few scientists and engineers who were sent abroad for training. In the meantime a small laboratory with limited facilities was set-up in Karachi. The actual implementation of the plans began soon after the appointment of Dr.Usmani as Chairman in March 1960. Recruitment and training of manpower gained momentum and two laboratories with good experimental facilities was set-up at Lahore and Dacca in 1961 and 1962 respectively. An Agriculture Research Centre at Tandojam and Nuclear Medical Centres at Karachi and Lahore was also set-up in early 1960’s. A multi disciplinary, Pakistan Institute of Nuclear Science and Technology was established in 1965 and a research reactor was installed which achieved first criticality in December 1965. In early 1960’s studies were undertaken to examine the technical and economic feasibility of establishing a nuclear power plant for the generation of electricity. The construction of Karachi Nuclear Power Plant started in the middle of 1967 and completed in early 1971. The first criticality of the reactor was achieved in August 1971 and the plant was formally commissioned in 1972. In the middle of 1970’s, embargo on the supply of materials and nuclear equipment by developed countries affected the programs of PAEC. This difficulty was overcome by developing a certain level of self-reliance and self-sufficiency in certain areas. PAEC, ever since 1960’s remained a dynamic organization and continued to make greater progress in the next decades.